Characteristics of Superficial Dermatomycosis Patients at RSUD Dr. H. Chasan Boesoirie Ternate in 2019-2022 - Khoir, Muhammad Fathul; Marsaoly, Ryan Rinaldy; Albaar, Thoha Muhajir (Syntax Corporation Indonesia, 2026)
Superficial dermatomycosis is the most common fungal skin disease in humans and is caused by dermatophytes and some opportunistic fungi. It is estimated to affect around 20–25% of the world’s population, and its incidence is increasing. The purpose of this study was to determine the characteristics of superficial dermatomycosis patients at RSUD Dr. H. Chasan Boesoirie Ternate from 2019 to 2022. This retrospective descriptive study used a proportional random sampling technique based on the population of superficial dermatomycosis patients who met the inclusion and exclusion criteria, and data collection was carried out using medical records. The results showed that, out of the 80 cases, the majority of patients were adults (63%), students (45%), and males (65%). The most common type of superficial dermatomycosis was tinea corporis (34%), and the most frequently administered treatment was combination therapy involving topical antifungals, systemic antifungals, and antihistamines (31%). In conclusion, most cases of superficial dermatomycosis occurred in adult males, with tinea corporis being the predominant type and combination therapy being the most common treatment approach.